Microstructural evolution and wear performance of Ti662 alloy reinforced with FeCoCrCuSi high entropy alloy using microwave sintering - S. Ragunath; N. Radhika; Adeolu Adesoji Adediran (Journal of Materials Research and Technology)
High Entropy alloy (HEA) is a potential reinforcement material to enhance the strength and wear behaviour of base materials through refined microstructure. In the present work, Ti6Al6V2Sn (Ti662 alloy) is reinforced with a ball-milled equimolar FeCoCrCuSi HEA by the Microwave Sintering (MS) process. A reduced α-Ti and improved β-Ti phases along with a single-phase BCC structure are attained in the Ti662/HEA composite. The properties of MS-processed composite are further enhanced by annealing at 900 °C for 60 min. The annealed composite exhibits refined grains with a mean of 0.414 μm. The annealed composite possesses exceptional microhardness of 796 HV, which is 3.2 and 1.6 times higher than the Ti662 alloy and Ti662/HEA composite. The pin-on-disc tribometer is used to conduct the wear analysis under varying process parameters. The reduced wear rate is attained in the Ti662/HEA annealed composite owing to the grain refinements, improved densification, and least porosity over the Ti662 alloy and Ti662/HEA composite. The wear mechanism including delamination, formation of the oxide layer, and severe grooves of annealed composite is revealed by worn surface morphology.